Black carbon in the Southern Andean snowpack - Cordero, Raul R.; Sepulveda, Edgardo; Feron, Sarah; Wang, Chenghao; Damiani, Alessandro; Fernandoy, Francisco; Neshyba, Steven; Rowe, Penny M.; Asencio, Valentina; Carrasco Cerda, Jorge Fernando; Alfonso, Juan A.; MacDonell, Shelley; et al. (My University, 2022)
The Andean snowpack is an important source of water for many communities. As other snow-covered regions around the world, the Andes are sensitive to black carbon (BC) deposition from fossil fuel and biomass combustion. BC darkens the snow surface, reduces the albedo, and accelerates melting. Here, we report on measurements of the BC content conducted by using the meltwater filtration (MF) technique in snow samples collected across a transect of more than 2500 km from the mid-latitude Andes to the southern tip of South America. Addressing some of the key knowledge gaps regarding the effects of the BC deposition on the Andean snow, we identified BC-impacted areas, assessed the BC-related albedo reduction, and estimated the resulting snow losses. We found that BC concentrations in our samples generally ranged from 2 to 15 ng g(-1), except for the nearly BC-free Patagonian Icefields and for the BC-impacted sites nearby Santiago (a metropolis of 6 million inhabitants). We estimate that the seasonal snowpack shrinking attributable to the BC deposition ranges from 4 mm water equivalent (w.e.) at relatively clean sites in Patagonia to 241 mm w.e. at heavily impacted sites close to Santiago.
Keywords: snow; black carbon; andes